A Superhydrophobic Sponge with Hierarchical Structure as an Efficient and Recyclable Oil Absorbent. Issue 9 (26th May 2015) - Liu, Qin; Meng, Kai; Ding, Kui; Wang, Yaobing
Abstract Oil/water separation is a worldwide challenge due to frequent oil spillages, and high‐performance absorbents are in high demand. In this work, a superhydrophobic sponge was fabricated by the polymerization of aniline, with subsequent simple immersion in n‐dodecylthiol. The polyaniline (PANI) constructed a nanoscale rough surface on the three‐dimension (3D) network of melamine sponge while n‐dodecylthiol reduced surface energy, thus lead to the superhydrophobicity. This superhydrophobic sponge could absorb a broad spectrum of oil and organics efficiently, with the highest 122 times of its own weight absorption capacity. Owing to the strong mechanical elasticity inherited from the pristine melamine sponge and stable adhesion of PANI, this sponge exhibited good recyclability through squeezing. More importantly, the fabrication procedure is facile, low‐cost and easily scalable. Thus, this superhydrophobic sponge is highly promising for absorption oil from water.